Evaluación de la aplicación de agua ozonificada en el lavado de Chocho en los materiales genéticos andino y nativo (lupinus mutabilis sweet) y su comportamiento en pos cosecha, en la provincia de Cotopaxi, Campus Experimental Salache. - Lema Chacha, Richard Guillermo. (2021)
In the present investigation, the postharvest behavior of two genetic materials of Lupinus mutabilis (Var. Andino 451 and Local Native Ecotype) and the use of ozonated water (O3) in three doses (0.0ppm, 0.35ppm, and 0.48ppm) were evaluated. in the washing process to debitter them. For which a DBCA was used with a 2x3 factorial arrangement with 3 repetitions and 18 experimental units. The following results were obtained: the best genetic material was the native Local ecotype with 0.22% alkaloids in the third wash. The best concentration was 0.48 with 0.18% alkaloid in the third wash and the best treatment T3 (native local ecotype with 0.48ppm dose) with 0.22% alkaloid in the third wash. Regarding the indicators evaluated in postharvest on the sixth day of storage under environmental conditions, the best treatment was T3 with 67.44% humidity; 14.81% ash; 7.54 pH; firmness 3 Kg / cm3; 24.71 g of weight; and 0% presence of pests and diseases.